Global geomagnetically induced currents during quiet geomagnetic activity on 23 December 2014 / Farah Adilah Mohd. Kasran, Mohamad Huzaimy Jusoh and Siti Amalina Enche Ab Rahim - Mohd. Kasran, Farah Adilah; Jusoh, Mohamad Huzaimy; Enche Ab Rahim, Siti Amalina (UiTM Press, 2018)
In this study, the global GIC activity was investigated during the sudden impulse (SI) event associated with coronal mass ejection (CME) passage on 23 December 2014 in order to assess the GIC risks at different latitudes even without any strong geomagnetic activity. Firstly, the solar wind parameters, namely, solar wind speed (Vsw) and solar wind dynamic pressure (Pdyn), interplanetary magnetic field (IMF) Bz component, the auroral electrojet (AU and AL index) and SYM H index that represents the ring current are thoroughly studied for two days, during the SI event and after the event. Then, the temporal variation of SYM H was extracted to estimate the level of Earth’s magnetospheric compression associated with the interplanetary shock. The global latitudinal temporal changes of magnetic field H-component during the SI event were statistically analyzed to observe its impact to the global GIC. The same method of analysis was then further examined in consideration of local time (LT) and the SI event period to identify the time corresponded to the strong impact of GIC activity. The results revealed an interesting finding where a comparable equatorial GIC activity with GIC activity in high latitude region occurred during the arrival of interplanetary shock due to the SI event. Besides, the result also gave the idea on important timing for large GIC prediction in particular area.